Proximal renal tubular acidosis mediated by mutations in NBCe1-A: unraveling the transporter's structure-functional properties - Kurtz, Ira; Zhu, Quansheng (Frontiers in Physiology, 2013)
NBCe1 belongs to the SLC4 family of base transporting membrane proteins that plays a significant role in renal, extrarenal, and systemic acid-base homeostasis. Recent progress has been made in characterizing the structure-function properties of NBCe1 (encoded by the SLC4A4 gene), and those factors that regulate its function. In the kidney, the NBCe1-A variant that is expressed on the basolateral membrane of proximal tubule is the key transporter responsible for overall transepithelial bicarbonate absorption in this nephron segment. NBCe1 mutations impair transepithelial bicarbonate absorption causing the syndrome of proximal renal tubular acidosis (pRTA). Studies of naturally occurring NBCe1 mutant proteins in heterologous expression systems have been very helpful in elucidation the structure-functional properties of the transporter. NBCe1 mutations are now known to cause pRTA by various mechanisms including the alteration of the transporter function (substrate ion interaction, electrogenicity), abnormal processing to the plasma membrane, and a perturbation in its structural properties. The elucidation of how NBCe1 mutations cause pRTA in addition to the recent studies which have provided further insight into the topology of the transporter have played an important role in uncovering its critically important structural-function properties.